The CH4/NO/O2 “Lean-deNOx” Reaction on Mesoporous Mn-Based Mixed Oxides - Stathopoulos, Vassilis; Costa, Costas; Pomonis, Phillippos J.; Efstathiou, A. M. (My University, 2001)
High surface area Mn-based porous oxides (MANPO) containing additives like Ce, Sr and La were found to be very active and selective materials under 0.67% CH4/0.2% NO/5% O2 “lean-deNO x ” conditions in the 200–300°C low-temperature range. These materials perform also impressively in the presence of 4% H2O in the feed stream, where a N2 selectivity of 98% and an excellent stability over 24 h on stream have been observed. The MANPO materials can be considered serious competitors of noble metals for low-temperature “lean-deNO x ” applications.
Keywords: Lean-deNOx; NO reduction; NO TPD